DA PERVERSÃO NOSSA DE CADA DIA ÀS GRANDES PERVERSÕES DO SEXUAL - Roberto Ceccarelli, Paulo (POLÊM!CA, 2015)
Resumo: A partir do sexual freudiano, o texto aborda a questão da perversão dentro da perspectiva freudiana no trabalho de cultura (Kulturarbeit). Para Freud, uma das maneiras de se entender as perversões leva em conta a não "domesticação" das pulsões pelo trabalho da cultura. Nessa perspectiva, discutir-se-á as potencialidades de perversão, da perversão nossa de cada dia às grandes perversões do sexual passando pela perversão do outro lado do divã, assim como a posição do analista na escuta das perversões. Palavras-chave: Trabalho de cultura. Pulsão. Destinos pulsionais. Perversões. FROM OUR DAILY PERVERSION TO THE GREAT PERVERSIONS OF THE SEXUAL Abstract: In this work, the author discusses, starting form Freud's description of the sexual, perversion from the Freudian perspective of the work of culture (Kulturarbeit). For Freud, one of the ways to understand perversion takes into account the non "domestication" of the drives by the work of culture. In this perspective, the potential to perversions will be discussed from our dailyperversion, to the great perversions of the sexual, including the perversion on the other side of the couch. Also, same considerations of the position of the analyst when hearing to perversions will be brought upon. Keywords: Work of culture. Drive. Drives destiny. Perversions.